Combination therapy with remdesivir and immunomodulators improves respiratory status in COVID‐19: A retrospective study. Issue 12 (8th August 2022) - Kojima, Yuichi; Nakakubo, Sho; Kamada, Keisuke; Yamashita, Yu; Takei, Nozomu; Nakamura, Junichi; Matsumoto, Munehiro; Horii, Hiroshi; Sato, Kazuki; Shima, Hideki; Suzuki, Masaru; Konno, Satoshi
Abstract: Immunomodulators (tocilizumab/baricitinib) improve outcomes of coronavirus disease 2019 (COVID‐19) patients, but the synergistic effect of remdesivir is unknown. The effect of combination therapy with remdesivir, immunomodulators, and standard treatment in COVID‐19 patients was investigated. This retrospective, single‐center study included COVID‐19 patients who were treated with tocilizumab or baricitinib. The severity of respiratory status in the two groups on Days 14 and 28 and the duration to respiratory recovery in both groups were compared, and the effect of remdesivir use on respiratory status was examined in a multivariate analysis. Ninety‐eight patients received tocilizumab or baricitinib; among them, 72 used remdesivir (remdesivir group) and 26 did not (control group). The remdesivir group achieved faster respiratory recovery than the control group (median 11 vs. 21 days, p  = 0.033), faster weaning from supplemental oxygen (hazard ratio [HR]: 2.54, 95% confidence interval [CI]: 1.14–5.66, p  = 0.021). Age, body mass index, diabetes mellitus, and time from onset to oxygen administration were independent prognostic factors. The remdesivir group achieved better severity level at Days 14 and 28 ( p  = 0.033 and 0.003, respectively) and greater improvement from baseline severity ( p  = 0.047 and 0.018, respectively). Remdesivir combination therapy did not prolong survival (HR: 0.31, 95% CI: 0.04–2.16, p  = 0.23). Among severely ill COVID‐19 patients who received immunomodulator, remdesivir contributed to a shorter respiratory recovery time and better respiratory status at Days 14 and 28. Concomitant remdesivir with immunomodulators and standard treatment may provide additional benefit in improving respiratory status of COVID‐19 patients.